a: \(A=\dfrac{\left(x-y\right)^2}{xy}=\dfrac{\left(3+\dfrac{1}{2}\right)^2}{3\cdot\dfrac{-1}{2}}=\dfrac{49}{4}:\dfrac{-3}{2}=\dfrac{49}{4}\cdot\dfrac{-2}{3}=\dfrac{-49}{6}\)
b: Trường hợp 1: x=1
\(B=\dfrac{2\cdot1^2+3\cdot1\cdot\left(-2\right)^2}{4\cdot1+5\cdot\left(-2\right)}=\dfrac{-10}{-6}=\dfrac{5}{3}\)
Trường hợp 2: x=-1
\(B=\dfrac{2\cdot\left(-1\right)^2+3\cdot\left(-1\right)\cdot\left(-2\right)^2}{4\cdot\left(-1\right)+5\cdot\left(-2\right)}=\dfrac{5}{7}\)
c: |x-1|=2
=>x-1=2 hoặc x-1=-2
=>x=3 hoặc x=-1
Thay x=3 vào C, ta được:
\(C=4\cdot3^2+9\cdot3-5=4\cdot9+27-5=58\)
Thay x=-1 vào C, ta được:
\(C=4\cdot\left(-1\right)^2+9\cdot\left(-1\right)-5=4-5-9=-10\)